WIRELESS NETWORKED CONTROL SYSTEM (WNCS) FOR PRESSURE SYSTEM - MOHAMAD NAZRI, MAIZATUL FARHANA (IRC, 2019)
Networked Control System has been introduced in several industries, such as automotive system, manufacturing and chemical processess. It is of interest because of its flexibility and cost effectiveness. However, this approach faces drawbacks such as process deadtime, network and computational delays. The purpose of this project is to build a Wireless Network Control System (WNCS) loop structure where different PID controllers are implemented. The performance of each controller are analyzed in terms of transient and steady-state responses. The WNCS structure is constructed based on a transmitter and a pressure control valve connected to controller which consist of National Instrument (NI) Wireless DAQ Analog Input (AI) and Analog Output (AO) modules. Plant model is obtained from experimental result using empirical method. First-order with dead time (FOPDT) process model is used to find PID controller tuning parameters using either Ziegler-Nichols or Normalized PID. The controllers are simulated using MATLAB Simulink and the result are then compared. The best performance with acceptable error are used as WNCS controller using LabView. The result obtained from these experiments shows that Ziegler-Nichols method produce better performance as compared to Normalized PI.